Altitude acclimatization, training and performance - Green, H. J. (Journal of Science and Medicine in Sport, 2000)
Exposure to altitude results in a reduction in partial pressure of oxygen in the arterial blood and a reduction in oxygen content. In an attempt to maintain aerobic metabolism during increased effort, a series of acclimatization responses occur. Among the most conspicuous of these responses is an increase in hemoglobin (Hb) concentration. The increase in Hb has been construed as the fundamental adaptation enabling increases in aerobic power and performance to occur on return to sea-level. However, the use of altitude to boost training adaptations and improve elite sea-level performance, although tantalizing, is largely unproven. The reasons appear to be many, ranging from the poor experimental designs employed, to the numerous strategies designed to manipulate the altitude experience and the large inter-individual differences in response patterns. However, other factors may also be important. Acclimatization has also been shown to induce alteration in selected properties of the muscle cell, some of which may be counterproductive. The processes involved in cation cycling, as an example, appear to be down-regulated. Changes in these processes could impair certain types of performance.